2021
DOI: 10.2147/prbm.s336223
|View full text |Cite
|
Sign up to set email alerts
|

“I” Am Willing to Disclose, but “We” are Unwilling: The Impact of Self-Construal on Individuals’ Willingness to Disclose

Abstract: Purpose: In the big data era, many institutions (ie, hospitals) and firms use various methods to encourage people to disclose more personal information to gain competitive advantages in many businesses, such as healthcare and the Internet of Things (IoT) devices. Discussions on antecedents of individuals' willingness to reveal private data from individual differences perspective are limited. Drawing on information boundary theory, we examine how selfconstrual prompts a different regulatory focus (promotion foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…Previous researchers have found that higher selfefficacy are related to greater participation in health-promoting behaviors, and higher exercise intensity and frequency (Luszczynska et al, 2011;Dong et al, 2018). Furthermore, in an experimental study, self-efficacy was positively correlated with incremental health theory which was positively correlated with participation in health-related behavior, but negatively correlated with entity health theory which was negatively correlated with participation in health-related behavior (Zhang C. et al, 2021;Zhang N. et al, 2021). Van't Riet et al (2010) examined the influence of self-efficacy on skin self-examination on the effects of different framed skin-cancer detection information.…”
Section: The Moderating Effect Of Lay Theories Of Healthmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous researchers have found that higher selfefficacy are related to greater participation in health-promoting behaviors, and higher exercise intensity and frequency (Luszczynska et al, 2011;Dong et al, 2018). Furthermore, in an experimental study, self-efficacy was positively correlated with incremental health theory which was positively correlated with participation in health-related behavior, but negatively correlated with entity health theory which was negatively correlated with participation in health-related behavior (Zhang C. et al, 2021;Zhang N. et al, 2021). Van't Riet et al (2010) examined the influence of self-efficacy on skin self-examination on the effects of different framed skin-cancer detection information.…”
Section: The Moderating Effect Of Lay Theories Of Healthmentioning
confidence: 99%
“…Research on the information effects has shown that there is a positive correlation between perceived risk and willingness to share information with others. People with a higher level of perceived risk are more likely to engage in health protection behaviors ( Zhang C. et al, 2021 ; Zhang N. et al, 2021 ), and there is a significant correlation between risk perception and self-reported preventive health behaviors ( Dryhurst et al, 2020 ). In addition, researchers also found that the severity of perceived risk was associated with recommended behavioral changes ( Rubin et al, 2009 ).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Personal information and identifiability Zhang, et al define personal information as "any information relating to an identified or identifiable person" [18]. That is, when a person is identifiable, any information related to that person is personal information, and confidentiality is the basis for the empowerment of personal information.…”
Section: Data Security and Privacy Protectionmentioning
confidence: 99%
“…If the above-mentioned scheme for data collection, preservation, extraction, and use can be established, the secondary use of AI data can be achieved for the benefit of human health while ensuring patient privacy and data security. With the development of AI technology, the implementation of deidentification is not static, and the boundary between absolute anonymity and identifiable information is becoming increasingly blurred [18]. It is indeed difficult to achieve zero risk of identification as well as absolute and permanent anonymity.…”
Section: Data Extraction and Usementioning
confidence: 99%